Learning, memory deficits, and impaired neuronal maturation attributed to acrylamide. Issue 9 (3rd May 2018) - Lee, Seulah; Park, Hee Ra; Lee, Joo Yeon; Cho, Jung-Hyun; Song, Hye Min; Kim, Ah Hyun; Lee, Wonjong; Lee, Yujeong; Chang, Seung-Cheol; Kim, Hyung Sik; Lee, Jaewon
ABSTRACT: Acrylamide (ACR) is a neurotoxin known to produce neurotoxicity characterized by ataxia, skeletal muscle weakness, cognitive impairment, and numbness of the extremities. Previously, investigators reported that high-dose (50 mg/kg) ACR impaired hippocampal neurogenesis and increased neural progenitor cell death; however, the influence of subchronic environmentally relevant low dose-(2, 20, or 200 μg/kg) ACRs have not been examined in adult neurogenesis or cognitive function in mice. Accordingly, the aim of the present study was to investigate whether low-dose ACR adversely affected mouse hippocampal neurogenesis and neurocognitive functions. Male C57BL/6 mice were orally administered vehicle or ACR at 2, 20, or 200 μg/kg/day for 4 weeks. ACR did not significantly alter the number of newly generated cells or produce neuroinflammation or neuronal loss in hippocampi. However, behavioral studies revealed that 200 μg/kg ACR produced learning and memory impairment. Furthermore, incubation of ACR with primary cultured neurons during the developmental stage was found to delay neuronal maturation without affecting cell viability indicating the presence of developmental neurotoxicity. These findings indicate that although exposure to in vivo low-dose ACR daily for 4 weeks exerted no apparent marked effect on hippocampal neurogenesis, in vitro observations in primary cultured neurons noted adverse effects on learning and memory impairment suggestive of neurotoxic actions.